Characterization of depth perception information inferred from neuronal activity in primary visual cortex - Nuo Dong; Yuping Tan; Yuyuan Wang; Yumin Chen; Haibing Xu (PLoS ONE, 2025)
Depth perception is crucial for spatial awareness, enabling animals to interpret three-dimensional environments. Although the primary visual cortex (V1) is known to process depth information, the specific contributions of V1 neurons to various aspects of depth perception remain underexplored. In this study, we investigated how V1 neurons engage in both passive and active depth-related tasks, examining whether distinct neuronal populations support different aspects of depth processing. Using in vivo calcium imaging in freely moving mice, we observed that specific groups of V1 neurons are selectively active in passive (visual cliff) and active (depth discrimination) tasks, suggesting functional segregation within V1. Additionally, neurons in the primary visual cortex prefer encoding objective positions rather than egocentric distances in non-depth-based tasks. Moreover, egocentric distance discrimination, as reflected by the primary visual cortex, appears to be more prospective. These findings provide insight into V1’s versatility, highlighting its potential role in spatial navigation and decision-making.